Panisaspis, a new genus of pliomerid trilobites from the Lower Ordovician (Ibexian; Tulean and Blackhillsian) of the Great Basin, western USA - Mcadams, Neo E.b.; Adrain, Jonathan M. (Zootaxa, 2011)
Panisaspis n. gen. is a clade of pliomerid trilobites from the Tulean and Blackhillsian stages (Floian) of the Great Basin.  It includes Protopliomerops? quattuor Hintze, 1953, and ten new species, six of which are formally named: Panisaspis millardensis (type species), P. sevierensis, P. deltaensis, P. rancherensis, P. topscityensis, and P. loganensis.  Four new species are not well enough known for formal naming and are described in open nomenclature.  All species are Tulean in age except for P. millardensis, which is earliest Blackhillsian.  Synapomorphies of Panisaspis include a short, nearly semicircular anterior border; small L1; large genal spines; a rounded, ovoid hypostomal border; elongated third pygidial spines; and a large, triangular terminal piece with distinct pitted impressions.  Phylogenetic analysis indicates that P. millardensis and P. sevierensis are sister taxa, and that P. deltaensis, P. rancherensis, P. topscityensis, P. quattuor, and P. loganensis are successive sister species.  The group may be sister to Ibexaspis Přibyl and Vaněk in Přibyl et al., 1985.